Phenotyping Young GluA1 Deficient Mice – A Behavioral Characterization in a Genetic Loss-of-Function Model - Reiber, Maria; Stirling, Helen; Sprengel, Rolf; Gass, Peter; Palme, Rupert; Potschka, Heidrun (Frontiers in Behavioral Neuroscience, 2022)
Alterations of glutamatergic neurotransmission have been implicated in neurodevelopmental and neuropsychiatric disorders. Mice lacking the GluA1 AMPA receptor subunit, encoded by the Gria1 gene, display multiple phenotypical features associated with glutamatergic dysfunction. While the phenotype of adult GluA1 deficient (Gria1-/-) mice has been studied comprehensively, there are relevant gaps in knowledge about the course and the onset of behavioral alterations in the Gria1 knockout mouse model during post-weaning development. Based on former investigations in young wild-type mice, we exposed female and male adolescent Gria1-/- mice to a behavioral home-cage based testing battery designed for the purpose of severity assessment. Data obtained from mice with a constitutive loss of GluA1 were compared with those from wild-type littermates. We identified several genotype-dependent behavioral alterations in young Gria1-/- mice. While the preference for sweetness was not affected by genotype during adolescence, Gria1-/- mice displayed limited burrowing performance, and reached lower nest complexity scores. Analysis of home-cage based voluntary wheel running performance failed to confirm genotype-dependent differences. In contrast, when exposed to the open field test, Gria1-/- mice showed pronounced hyperlocomotion in early and late adolescence, and female Gria1-/- mice exhibited thigmotaxis when prepubescent. We found increased corticosterone metabolite levels in fecal samples of adolescent Gria1-/- mice with females exhibiting increased adrenocortical activity already in prepubescence. Considering the course of behavioral modifications in early and late adolescence, the results do not support a persistent level of distress associated with GluA1 deficiency in the line. In contrast, the laboratory-specific readouts indicate transient, mild impairments of behavioral patterns relevant to animal welfare, and suggest a mild overall burden of the line.